Education and training in food science : a changing scene - Morton, I. D. (Woodhead Publishing Ltd, 1991)
This book reviews the need for increased training in the food industry in order to bridge the gap between Eastern and Western Europe and the USA. Higher education in food science is discussed, including the training of technicians, and European initiatives, including ERASMUS and Network, are also described.